Monday

March 2, 2015

March 2, 2015

Posted by **gopi** on Saturday, January 12, 2013 at 11:14pm.

- math -
**Bosnian**, Sunday, January 13, 2013 at 12:49amcos ^ 2 ( x ) - sin ^ 2 ( x ) = cos ( 2x )

2 sin ( x ) cos ( x ) = sin ( 2 x )

Equation :

cos ^ 2 ( x ) - 2 sin( x ) cos( x ) -

sin ^ 2 ( x ) = 0

we can write like :

cos ( 2 x ) - sin ( 2 x ) = 0 Add sin ( 2 x ) to both sides

cos ( 2 x ) - sin ( 2 x ) + sin ( 2 x ) = 0 + sin ( 2 x )

cos ( 2 x ) = sin ( 2 x ) Divide both sides by cos ( 2 x )

cos ( 2 x ) / cos ( 2 x ) = sin ( 2 x ) / cos ( 2 x )

1 = tan ( 2 x )

tan ( 2 x ) = 1

tan ( pi / 4 ) = 1

Tangent is a periodic function with period pi , so :

2 x = n pi + pi / 4

( n is an integer ) Divide both sides by 2

x = n pi / 2 + pi / 8

**Answer this Question**

**Related Questions**

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Math (trigonometric identities) - I was given 21 questions for homework and I ...

Trigonometry - Prove the following trigonometric identities. please give a ...

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Precalculus/Trig - I can't seem to prove these trig identities and would really ...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

trig - express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

calculus - Could someone check my reasoning? thanx Find the derivative of the ...

Trig - prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= ...